Spatial architecture of regulatory T-cells correlates with disease progression in patients with nasopharyngeal cancer - Zhou, Fengge; Shayan, Gulidanna; Sun, Shiran; Huang, Xiaodong; Chen, Xuesong; Wang, Kai; Qu, Yuan; Wu, Runye; Zhang, Ye; Liu, Qingfeng; Zhang, Jianghu; Luo, Jingwei; et al. (Frontiers in Immunology, 2022)
Purpose: This study aims to investigate the prognostic value of composition and spatial architecture of tumor-infiltrating lymphocytes (TILs) as well as PDL1 expression on TILs subpopulations in nasopharyngeal carcinoma (NPC). Methods: A total of 121 patients with NPC were included and divided into two groups: favorable (n = 68) and unfavorable (n = 53). The archived tumor tissues of the included patients were retrieved, and a tissue microarray was constructed. The density and spatial distribution of TILs infiltration were analyzed using the multiplex fluorescent immunohistochemistry staining for CD3, CD4, CD8, Foxp3, cytokeratin (CK), PDL1, and 4′,6-diamidino-2-phenylindole (DAPI). The infiltration density of TILs subpopulations and PDL1 expression were compared between the two groups. The Gcross function was calculated to quantify the relative proximity of any two types of cells. The Cox proportional hazards regression model was used to identify factors associated with overall survival (OS) and disease-specific survival (DFS). Results: The densities of regulatory T-cells (Tregs), effector T-cells (Teffs), PDL1+ Tregs, and PDL1+ Teffs were significantly higher in patients with unfavorable outcomes. PDL1 expression on tumor cells (TCs) or overall TILs was not associated with survival. Multivariate analysis revealed that higher PDL1+ Tregs infiltration density was independently associated with inferior OS and DFS, whereas Tregs infiltration density was only a prognostic marker for DFS. Spatial analysis revealed that unfavorable group had significantly stronger Tregs and PDL1+ Tregs engagement in the proximity of TCs and cytotoxic T lymphocyte (CTLs). Gcross analysis further revealed that Tregs and PDL1+ Tregs were more likely to colocalize with CTLs. Moreover, increased GTC:Treg (Tregs engagement surrounding TCs) and GCTL:PDL1+ Treg were identified as independent factors correlated with poor outcomes. Conclusion: TILs have a diverse infiltrating pattern and spatial distribution in NPC. Increased infiltration of Tregs, particularly PDL1+ Tregs, as well as their proximity to TCs and CTLs, correlates with unfavorable outcomes, implying the significance of intercellular immune regulation in mediating disease progression.